Effectiveness of Problem Based Learning Model in Enhancing Motivation to Learn Fiqh among MTs Al Khoziny Students - Su'eb, Su'eb; Masuwd, Mowafg Abrahem (Medan Resource Center, 2025)
The issue of education in pesantren has attracted considerable attention. As centers of religious learning, pesantren have produced many experts in the field of religion. This study aims to enhance the learning motivation of seventh-grade second-semester students at MTs Al Khoziny Buduran Sidoarjo through the implementation of the Problem Based Learning (PBL) model, which emphasizes critical, analytical, systematic, and logical thinking in problem-solving. This model is expected to foster students’ motivation and scientific attitudes, with the teacher acting as a facilitator to guide students in the problem-solving process. This research is a Classroom Action Research (CAR) conducted in two cycles, involving 28 students as research subjects. Data on students’ motivation in learning Fiqh were collected through questionnaires and analyzed using descriptive statistical analysis. The results showed that in the first cycle, the average student score was 70 (categorized as sufficient), with an absorption rate of 70% and classical completeness of 50%. In the second cycle, the average score increased to 82 (categorized as good), with an absorption rate of 82% and classical completeness of 92%. Based on these findings, it can be concluded that the Problem Based Learning model is effective in improving the learning motivation of seventh-grade second-semester students in Fiqh at MTs Al Khoziny Buduran Sidoarjo.